Differences between echocardiography and cardiac nuclear magnetic resonance parameters in children with bicuspid aortic valve-related aortopathy - Stasa Krasic; Stasa Krasic; Boris Zec; Vesna Topic; Sasa Popovic; Dejan Nesic; Marija Zdravkovic; Vladislav Vukomanovic; Vladislav Vukomanovic (Frontiers in Cardiovascular Medicine)
ObjectivesThe bicuspid aortic valve (BAV) is the most common congenital heart defect. Patients with BAV frequently develop aortopathy, which depends on the dysfunction and morphotype of the BAV.AimThe aim of our study was to compare the echocardiography and cardiac magnetic resonance (CMR) findings in BAV patients, and to define the risks of BAV dysfunction and aortopathy.MethodsThe retrospective study included 50 patients (68% male) with BAV, with an average age of 13.6 ± 3.9 years, who underwent a transthoracic echocardiographic examination and CMR at our institute from 2012 to 2020.ResultsThe BAV types were evaluated significantly differently by echocardiography and CMR (p = 0.013). 54% of patients had BAV insufficiency on echo and 70% on echo CMR. It was more prevalent in males, older patients, and patients with a higher body surface area. By comparing the degree of insufficiency measured by echo (1+, IQR 0–1), and CMR (0, IQR 0–1), a significant difference was observed (p = 0.04), while a moderate positive correlation was proved (rr = 0.4; p = 0.004). Stenosis was registered in 44% of patients by echo, while 58% had stenosis on CMR. The peak pressure gradient measured by echo was significantly higher than the velocity on CMR (41, IQR 22.7–52.5 mmHg vs. 23, IQR 15.5–35.0 mmHg; p = 0.002). Aortopathy was registered in 76% of patients on echo and 78% on CMR; 38% of patients had severe aortic dilatation on echo and 54% on CMR (p = 0.003). Patients with BAV stenosis on echo had more frequent dilatation of the tubular ascending aorta (15/24 pts; p = 0.02). All patients with BAV insufficiency on CMR had aortopathy (p = 0.04) and had enlargement of the sinus of Valsalva and sinotubular junction. In patients with associated coarctation, the development of aortopathy occurred less frequently than those without coarctation (7/39 vs. 32/39; p = 0.003). The Bland-Altman method, a specific type of scatterplot that is used to visualize the results of comparing two measures, demonstrated the existence of agreement between the two methods, and a level of agreement between the methods of 95% was demonstrated.ConclusionOur study indicated significant differences in the measured BAV morphotype and dysfunction when comparing the two diagnostic methods. On the other hand, moderate to strong correlations were found in the evaluated parameters, which indicates the importance of performing noninvasive diagnostic procedures in the follow-up of these patients.